Atlas of world history (Oxford University Press, 1999)
Description Not Provided

Atlas of the world (World Book, Inc, 2013)
Description Not Provided
World , North America , South America , Africa , Europe , Asia , Australasia & Oceania , Index & gazeteer.

National Geographic historical atlas of the United States (National Geographic, 2004)
Description Not Provided
An age of rediscovery, 1400-1749 , New people in a new world, 1750-1799 , Forming a more perfect union, 1800-1849 , A nation comes of age, 1850-1899 , A nation at war, 1900-1949 , Decades of change, 1950-present.

Great city maps (DK, 2016)
"Journey back in time and take a walk through the historic streets of the world’s greatest cities. Great City Maps is the companion title to DK’s Great Maps and takes a focused look at over 70 gorgeously illustrated historical maps and plans of cities around the globe. Dive into the details of each beautiful map and learn about interesting features with visual tours of the maps’ highlights – such as the Old London Bridge of London in 1572 and the orchards of Brooklyn in 1767 New York. Cities are centers of civilization and the way their maps portray them reflects their politics, religion, and culture. See how certain cities, and cartographic techniques, changed over time. More than just a bird's-eye view, this irresistible book tells the tales behind the cities from the hubs of ancient peoples to modern mega-cities, and profiles the iconic cartographers and artists who created each map. Perfect for history, geography, and cartography enthusiasts and a stunning gift for armchair explorers of all ages, Great City Maps is your window into the world's most fascinating cities."--